Model Kesetaraan Gender Di Arena Politik (Studi Penguatan Posisi Perempuan Dalam Politik di Kabupaten Aceh Utara) - Cut Sukmawati; Murniati Murniati; Ferizaldi Ferizaldi (Jurnal Transformasi Administrasi, 2014)
This paper is aiming at explorer the phenomenon of political representation of women in the 2014 legislative elections in Aceh. In the tradition of patriarchal culture, "politics" is claimed as the world of man because it is regarded as public domain with full of fight, hard, and give a certain social value (prestige) to the culprit. Political patriarchal society deemed incompatible with the spirit of women who they consider feminine. This study was conducted in North Aceh district, using a qualitative approach, through in-depth interviews, focus groups, observation and document review. Analyzing women in legislative elections in 2014 also Acehnese society perspectives on women's issues, particularly their participation in politics, as well as the limitations / barriers that women experience when a role in politics. Findings from the field indicate that the representation of women is the same as the 2009 legislative elections last April. The cause of this phenomenon include the internal issues related to women candidates in self motivation, passion or ambition they are, financially, on the other hand it is also due to the influence of the patriarchal culture in the society. In his own party, although the rules require women in legislative elections must meet the 30% quota, but the board majority party men are not really serious about supporting women candidates to be elected in April 2014 legislative elections. It is presented a mistaken understanding of the prohibition for women to enter politics into the religious context is also a great stumbling block for women, although there are people who understand that women also have equal opportunity with his brother.